Rare Concomitant Myxoid and Cystic Degeneration of Uterine Leiomyoma - Case Report - Samardjiski, Igor; Petrushevska, Gordana; Simeonova Krstevska, Slagjana; Paneva, Iva; Livrinova, Vesna; Todorovska, Irena; Ilieva Pejkovska, Maja; Dimitrovski, Sasho; Nikoloska, Katerina (Scripta Medica, 2021)
The uterine leiomyomas are monoclonal tumours of myometrial smooth muscle cells that are oestrogen dependent. A 43-year-old patient was referred by her gynaecologist under a suspected diagnosis of ovarian tumour. She complained of prolonged and profuse, regular menstrual bleeding that leaded to anaemia. The ultrasound examination showed a complex tumour mass with dimensions 68 x 85 mm, with several cystic formations fulfilled with clear fluid, which protrudes from the posterior wall of the uterus. Therefore, the diagnosis of leiomyoma with a cystic degeneration was considered preoperatively. In the case of cystic degeneration of the myoma, the ultra- sound shows a combination of cystic and solid components with irregular shape and variable echogenicity. The ovarian malignancy should be ruled out in the presence of a large cystic mass with irregular septa and solid nodular parts filling the small pelvis. Ultrasound characteristics of degenerative myomas should always be considered, so as not to replace it with an ovarian mass, especially if it is subserosal and on the loop.